(3GdaUhd GdegeI aj CUhd GdGFeIs - (3eMeO Hf GdMSf Hf Ydj GdYGedj , GdMQ GdYGedj,J (B1104 (3g` s ((3GHQGgje GdeTgOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YQafG fHPg ef GdCUhd GdcdjI hHYO ajbhd GdabjQ Edi Gddg bO SCdfi HYV UdMGA GdaVdGA HJCdja cJGH jTJed Ydi GdCUhd GdcdjI s
(3BNQgG (B:s
(3HGH Cf cd LRY hHcGA ecQhg EdG eG GSJKfi MeO Hf GdMSf GdWhSi ai GdCeGdi bO ChQOJ eG JjSQ GjQGOI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B204s
Keywords: (3CUhd Gdabgs